Organizations as Actors: Microfoundations of Organizational Intentionality. Issue 3 (June 2020) - Little, Daniel
The article addresses the topic of "group agency" with respect to large organizations. It undertakes to analyze some of the concrete micro- and meso-level processes (microfoundations) through which large organizations arrive at collective "knowledge" and "action." The article makes use of the theory of strategic action fields to analyze processes of knowledge and the implementation of organizational intentions. The article describes some of the dysfunctions and disunities that should be expected from these individual-level processes, including principal–agent problems, conflicts of interests and priorities among organizational actors, loose coupling among subunits, and outcomes that are influenced by powerful outsiders. It argues for a limited conception of " bounded localistic organizational rationality " in which organizations have limited coherence, unity, and consistency over time in their beliefs and actions.